2009
DOI: 10.1111/j.1471-4159.2009.06369.x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation factor Xa activates thrombin in ischemic neural tissue

Abstract: Thrombin is involved in mediating neuronal death in cerebral ischemia. We investigated its so far unknown mode of activation in ischemic neural tissue. We used an in vitro approach to distinguish the role of circulating coagulation factors from endogenous cerebral mechanisms. We modeled ischemic stroke by subjecting rat organotypic hippocampal slice cultures to 30‐min oxygen (5%) and glucose (1 mmol/L) deprivation (OGD). Perinuclear activated factor X (FXa) immunoreactivity was observed in CA1 neurons after OG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Signaling through PAR-1 appears to mediate the process of brain damage in adult animal models of subarachnoid hemorrhage (SAH)1617. Previous rodent studies have shown that the interference with this pathway in primary astrocyte cultures1819 as well as in hippocampal slice cultures20 provided a potential target for therapeutic approach in maintaining vascular integrity following brain damage in rats2122.…”
mentioning
confidence: 99%
“…Signaling through PAR-1 appears to mediate the process of brain damage in adult animal models of subarachnoid hemorrhage (SAH)1617. Previous rodent studies have shown that the interference with this pathway in primary astrocyte cultures1819 as well as in hippocampal slice cultures20 provided a potential target for therapeutic approach in maintaining vascular integrity following brain damage in rats2122.…”
mentioning
confidence: 99%
“…Using a blood free in vitro approach, we previously showed that thrombin protein is detected on Western blots after ischemia modelled in vitro by OGD and that specific thrombin and Factor Xa inhibitors confer neuroprotection [17,31]. The results presented here make two further points:…”
Section: Resultsmentioning
confidence: 55%
“…In contrast, in brain slices that are subjected to ischemic conditions such as OGD, no circulating coagulation factors are involved and the time points examined were somewhat shorter. Thrombin that is generated in the brain cells rises (14, 15) and as a result PAR1, its own receptor, may first increase as a complementary step, but these receptors are then cleaved and internalized leading to reduced levels. It is hypothesized that inhibiting the levels of thrombin during acute stroke will normalize PAR1 levels at the 2–24 hour time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of this receptor by low concentrations of thrombin may have neuroprotective effects, while at higher concentrations thrombin has deleterious effects (711). In the setting of an acute ischemic stroke, high thrombin levels have been detected in the infarct area, possibly as a consequence of blood–brain barrier opening (12, 13) or as a result of its local synthesis in the brain (14, 15) or both. Functionally, thrombin has been shown to cause synaptic dysfunction (1519) and later, on vascular disruption, inflammatory response and neuronal damage (2022), through the activation of PAR1 (13, 20).…”
Section: Introductionmentioning
confidence: 99%